Monument 14, 3 : Savage drift - Laybourne, Emmy (Laybourne, Emmy. Monument 14, 2014)
The survivors of the Monument 14 have finally made it to the safety of a Canadian refugee camp, but Josie, separated from the group and trapped in a brutal prison camp for exposed Type Os, may lose hope unless her lost love Niko and his companions Astrid, Dean and Jake can rescue her.